A música na educação cristã clássica: concepções e perspectivas a partir do ensino de violino em uma escola confessional - Almeida, Juliana Mendonça de (2024)
The diversity of educational-musical practices has been recurrently highlighted by specialized literature over the past few years. Similarly, in the field of education, we have observed a growing interest, both practical and methodological, as well as investigative, in different perspectives of human development. In this context, we highlight here, as the central theme of this work, classical Christian education and violin teaching within the scope of basic education. The combination of these two educational dimensions takes place in a private confessional school of basic education in a city in northeastern Brazil, which, for the past three years, has been developing a classical Christian education proposal, including, among various other curricular components, violin teaching as a musician-formative dimension. Thus, based on research conducted between August 2022 and July 2024, this work presents and discusses its main results. The general objective of the research was to understand the main conceptions surrounding violin teaching within the context of a basic school that adopts classical Christian education as its educational project. To achieve this, a case study was conducted at the researched school, using the following data collection instruments: documentary research, bibliographic research, and semi-structured interviews. The main results indicated that the analyzed institution is in the process of structuring an ideal curricular matrix, implementing mandatory collective violin teaching in some school years, grounded in the school's Christian worldview. Additionally, it became evident that there is a need for specific musical training within the proposed educational project so that music teaching aligns coherently with its context. These results have led to the interpretation that music education within classical Christian education is a current reality, aiming to meet the demands of society in an inclusive way, encouraging the development of further research on the subject.